Changes in the Oil Maantaan Tradition: Case Study in the Community of Nagari Ampuan Lumpo District IV Jurai Pesisir Selatan Regency, West Sumatra Province: Case Study in the Community of Nagari Ampuan Lumpo District IV Jurai Pesisir Selatan Regency, West Sumatra Province - Sitepu, Femi Baharnah; Yurisman; rizalpiliang84@gmail.com (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research aims to explain the procession of the oil maantaan tradition as well as changes in the oil maantaan tradition. The theory used in this research is Gillin's Theory of Social Change. The method used in this research is a case study method with a qualitative approach. The results of this research show that the oil maantaan tradition consists of 4 stages. The first stage is maucok (inviting) the nagari community. Second, fill the tray. The third stage is delivering the oil (baggage) from the bako party to the pangka (the baby's parents). At the end of the procession, the oil is handed over to the pangka. However, over time, this tradition has also changed. These changes can be seen from the implementation stage, especially the items brought by the community in this tradition. These items include kerosene which is replaced with long cloth, betel leaves replaced with the use of gulo-gulo, the addition of gold in luggage, and transportation.